The impact of impact evaluation: Are impact evaluation and impact evaluation synthesis contributing to evidence generation and use in low- and middle-income countries? - Richard Manning; Ian Goldman; Gonzalo Hernández Licona (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
In 2006 the Center for Global Development's report 'When Will We Ever Learn? Improving lives through impact evaluation' bemoaned the lack of rigorous impact evaluations. The authors of the present paper researched international organizations and countries including Mexico, Colombia, South Africa, Uganda, and Philippines to understand how impact evaluations and systematic reviews are being implemented and used, drawing out the emerging lessons. The number of impact evaluations has risen (to over 500 per year), as have those of systematic reviews and other synthesis products, such as evidence maps. However, impact evaluations are too often donor-driven, and not embedded in partner governments. The willingness of politicians and top policymakers to take evidence seriously is variable, even in a single country, and the use of evidence is not tracked well enough. We need to see impact evaluations within a broader spectrum of tools available to support policymakers, ranging from evidence maps, rapid evaluations, and rapid synthesis work, to formative/process evaluations and classic impact evaluations and systematic reviews.
Keywords: D04; O12; P45; 330; Entwicklungsländer; Developing countries; Entwicklungsprojekt; Development projects